Bibliometric and visual analysis of time-restricted eating - Wang, Shuai; Lin, Xiaoxiao; Guan, Yihong; Huang, Jinyu (Frontiers in Nutrition, 2022)
An increasing number of studies have shown the effects of time-restricted eating (TRE) on metabolic diseases and cardiovascular diseases associated with obesity. However, no bibliometric analyses were conducted in this field systematically. we aimed to visualize the publications about TRE to determine the frontiers and hotspots and then provide references and guidance for further studies. VOSviewer 1.6.16 was adopted to perform the bibliometric analysis. In our study, a total of 414 publications were included. A total of 2016 authors contributed to this field. The most productive authors were Satchidananda Panda, Krista A Varady and Emily NC Manoogian. All publications were distributed from about 624 organizations from 49 Countries/Regions. The leading institutions were the Salk Institute for Biological Studies, the University of California San Diego and the University of Alabama at Birmingham, and the most productive countries were the USA, the People's Republic of China and Japan. All publications were from 182 journals, and the most productive journals were Nutrients, Frontiers in Nutrition and Cell Metabolism. The first highest cited reference with 991 citations was published in Cell Metabolism, and authored by Satchidananda Panda et al. There were four indicating research directions, and the keywords of the green cluster were time-restricted feeding, metabolism, circadian clock, and circadian rhythm. The keywords of the blue cluster were obesity, health, diet, and food intake. The keywords of the red cluster were intermittent fasting, weight loss, caloric restriction, and time-restricted eating. The keywords of the yellow cluster were insulin resistance, metabolic disease, cardiovascular disease, and caloric intake. The main research hotspots in the TRE field were TRE and circadian rhythm, TRE and obesity, TRE and metabolic disease, and TRE and cardiovascular disease. TRE represents new directions to evaluate the effects of the timing of eating on different diseases, especially obesity, Type 2 diabetes mellitus and cardiovascular disease. Previous studies have generated impressive data on the effects of TRE on metabolic diseases and cardiovascular diseases associated with obesity. More high-quality studies are needed to assess the mechanism and efficacy of TRE in a wide range of populations and diseases.